Synthesis and Anticancer Evaluation of Benzimidazole Derivatives Having Norbornene/Dibenzobarrelene Skeletons and Different Functional Groups - Capan, Irfan; Servi, Suleyman; Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu (Wiley-V C H Verlag Gmbh, 2020)
Two different anhydrides having norbornene and dibenzobarrelene skeletons were synthesized from Diels-Alder cycloaddition reactions using dienes such as anthracene and cyclopentadiene, and dienophiles like maleic acid and maleic anhydride. New benzimidazole derivatives bearing carboxamide, guanidine, and cyclic imide functional groups were obtained from these anhydrides. The compounds were investigated for their effects on MDA-MB-231 (Human breast cancer), A549 (Lung cancer), Ovcar3 (Human Ovarian cancer), and Panc1 (human pancreas cancer) cell lines using the MTT assay test. Compounds 4-8 demonstrated critical cytotoxic action against all cell lines.
Keywords: Benzimidazole; carboxamide; cyclic imide; cytotoxicity; drug design; dibenzobarrelene; medicinal chemistry; norbornene